Promoting "Moderasi Beragama" As A Unifying Community Value for The Youth - Dian Herdiana; Aqshal Septiano Baroga; Ariq Putra Fauzan (Salus Publica: Journal of Community Service, 2023)
The diversity of society, ranging from origin, culture, and economy to religion, should be addressed with mutual respect and tolerance, in which the concept of religious moderation as an approach to diversity in Indonesia is a value that should be understood and applied by all citizens, including youth as the next generation in the future. Based on this, this article describes promotional activities for the values of religious moderation for the youth in Bandung City. Activities are carried out from the planning and implementation to the evaluation stages. The result of the promotion of religious moderation is that it has raised awareness among youth about the essential values of religious moderation in everyday life. The youth understands that religious moderation in respecting differences and upholding the values of tolerance is the right way to strengthen a sense of harmonious togetherness among fellow citizens. Through this activity, youth will also be committed to consistently applying the values of religious moderation in various activities, from the family and school environments to the community environment where they interact.